An Open-Access Review to Determine Best Evidence-Based Practice for COPD - Beth Ann Walker; Heidi Breckner; Morgan Carrier; Wendy Pullen; Erin Reagan; Lisa Telfer; Taryn Zimmerman (Scholarworks @ WMU, 2016)
Background: The manifestation of Chronic Obstructive Pulmonary Disease (COPD) can have an enormous impact on individuals' areas of occupation, specifically activities of daily living. Occupational therapy (OT) practitioners have the ability to efficiently treat these clients using evidence-based interventions to achieve optimal functioning and quality of life. The purpose of this research study was to identify specific interventions supported by evidence for consumers with COPD using an open-access database for OT. Method: A thematic synthesis of 102 articles available on COPD via the open-access database OTseeker was used in this study. A constant comparison approach revealed seven descriptive themes for intervention including exercise, education, self-management, cognitive-behavioral therapy, complementary and alternative medicine therapy, breathing technique training, and nutrition. Results: For each theme, sub-themes were discussed and components of effective interventions were identified. Aspects of an evidence-based intervention program for individuals with COPD were outlined. Conclusion: Occupational therapists can use this evidence to thoroughly design well-rounded effective evidence-based intervention programs to enable individuals with COPD to live life to its fullest.